The conversion of nata de coco bacterial cellulose into cellulose nanofibers using high shear mixer with eco-friendly fluid dynamics method - Amun Amri; Diana Eka Putri; Dhina Febryza; Salsabilla Diva Voadi; Syelvia Putri Utami; Hussein A. Miran; M. Mahbubur Rahman (Universitas Negeri Padang, 2024)
Nanocellulose is widely applied in various fields due to its superior characteristics. Several methods have been developed to synthesize it, but they still have limitedness as being non-eco-friendly and inefficient use. Therefore, the synthesis of nanocellulose from sustainable sources is being developed using a simple and eco-friendly method. This study successfully produced a low viscosity gel suspension of cellulose nanofibers (CNF) from bacterial cellulose (BC) derived from Nata de Coco using a high shear mixer (HSM). The mixture of BC and water in a 1:1 ratio was processed with various rotational speeds and times in the HSM. The suspension result was characterized using an Ostwald viscometer, UV-vis spectrophotometer, lux meter, scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), particle size analyzer (PSA), and x-ray diffraction (XRD). Based on the characterization, it was confirmed that higher rotational speeds and extended processing times reduced the suspension viscosity and increased light transmittance, indicating a reduction in BC size to the submicron/nanometer scale. The best light transmittance was achieved with the HSM at 4500 rpm for 180 min, resulting in a viscosity drop from 232.67 mPa.s to 1.45 mPa.s. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis showed that the CNF retained its fibrous structure with nanometer-scale widths and high porosity without significant changes in crystallinity.